Clinicopathologic factors linked to oncologic outcomes for renal cell carcinoma with sarcomatoid dedifferentiation: A PRISMA-compliant systematic review and meta-analysis - Shan, Lisong; Shao, Xue; Gu, Liangyou; Wu, Minhong; Lin, Pengxiu; Yu, Zhiling; Chen, Qingsheng; Zhu, Daqing (Frontiers in Surgery, 2022)
Background: There are still differences in the prognostic factors of renal cell carcinoma with sarcomatoid dedifferentiation (sRCC). To evaluate important predictors of survival in patients with sRCC. Patients and methods: A comprehensive search of PubMed, Embase, and Cochrane Library was conducted to identify eligible studies. The endpoints embraced overall survival (OS), cancer-speciﬁc survival (CSS), and progression-free survival (PFS). Hazard ratios (HRs) and related 95% conﬁdence intervals (CIs) were extracted. Results: A total of 13 studies were included for analyses. The pooled results showed that high ECOG PS (HR 2.39, 95% CI 1.32-4.30; P = 0.004), high T stage (HR 2.18, 95% CI 1.66-2.86; P < 0.001), positive lymph node (HR 1.54, 95% CI 1.40-1.69; P < 0.001), distant metastasis (HR 2.52, 95% CI 1.99-3.21; P < 0.001), lung metastases (HR 1.45, 95% CI 1.16-1.80; P < 0.001), liver metastases (HR 1.71, 95% CI 1.30-2.25; P < 0.001), tumor necrosis (HR 1.78, 95% CI 1.14-2.80; P = 0.010), and percentage sarcomatoid ≥ 50% (HR 2.35, 95% CI 1.57-3.52; P < 0.001) were associated with unfavorable OS. Positive lymph node (HR 1.57, 95% CI 1.33-1.85; P < 0.001), high NLR (HR 1.16, 95% CI 1.04-1.29; P = 0.008) were associated with unfavorable CSS. High T stage (HR 1.93 95% CI 1.44-2.58; P < 0.001) was associated with unfavorable progression-free survival. Conclusions: A meta-analysis of available data identified important prognostic factors for CSS, OS, and PFS of sRCC, that should be systematically evaluated for patient counseling, risk stratification, and treatment selection.